PENGARUH SISTEM INFORMASI BERBASIS KOMPUTER DAN KEPERCAYAAN TERHADAP KINERJA INDIVIDUAL (STUDI EMPIRIS PERBANKAN DI KOTA MEDAN) - Henny Zurika (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
This study is empirical study conducted with the aim to test hypotheses about the impact of computer-based information system and reliance on individual performance. The data in this study were drawn from the banking company in the city of Medan